Characterization of surface-modified LiMn2O4 cathode materials with indium tin oxide (ITO) coatings and their electrochemical performance - Kim, Chang-Sam; Kwon, Soon-Ho; Yoon, Jong-Won (ELSEVIER SCIENCE SA, 2014)
Indium tin oxide (ITO) is used to modify the surface of LiMn2O4 by a sol-gel method in an attempt to improve its electrochemical performance at elevated temperatures. The surface-modified LiMn2O4 is characterized via XRD, FE-SEM, TEM, Auger electron spectroscopy (AES) and inductively coupled plasma-atomic emission spectroscopy (ICP-AES). The surface layer modified by substitution with indium was observed at a scale of several nanometers near the surface on LiMn2O4. The concentration of ITO for electrochemical performance was varied from 0.3 wt% to 0.8 wt%. The 0.5 wt% ITO coated LiMn2O4 showed the best electrochemical performance. This enhancement in electrochemical performance is mainly attributed to the effect of the surface layer modified through ITO, which could suppress Mn dissolution and reduce the charge transfer resistance at the solid electrolyte interface. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: HIGH-TEMPERATURE; CYCLING PERFORMANCE; ACTIVE MATERIAL; LITHIUM; SPINEL; IMPROVEMENT; STABILITY; BATTERIES; LI; CO